2022
DOI: 10.1371/journal.pgph.0000187
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence and turnover intention among the Bangladeshi female nurses after a year of pandemic: An exploratory cross-sectional study

Abstract: During the COVID-19 pandemic, workplace violence was widespread against healthcare personnel. Workplace violence (WPV) against nurses exhilarates their turnover intention (TI). The objective of this study was to investigate the association between workplace violence and turnover intention and also identify other factors associated with TI among Bangladeshi female nurses. An exploratory cross-sectional study was carried out among 881 female nurses between April 26 and July 10, 2021. The TI of the female nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…The 5-item Workplace Violence Scale (WPVS) was used to assess WPV against nurses [ 36 , 37 ]. Previous studies, including studies among healthcare professionals, used the WPVS [ 38 , 39 ], including studies conducted during the COVID-19 pandemic [ 14 ]. This scale reports five types of violence: physical attack, mental abuse, threat, verbal sexual harassment, and sexual assault.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-item Workplace Violence Scale (WPVS) was used to assess WPV against nurses [ 36 , 37 ]. Previous studies, including studies among healthcare professionals, used the WPVS [ 38 , 39 ], including studies conducted during the COVID-19 pandemic [ 14 ]. This scale reports five types of violence: physical attack, mental abuse, threat, verbal sexual harassment, and sexual assault.…”
Section: Methodsmentioning
confidence: 99%
“…There was an empirically demonstrated link between WPV and psychological issues; for example, those subjected to WPV had a higher prevalence of depression than those not [ 13 ]. According to a recent study in Bangladesh, the overall prevalence of WPV among female nurses was 74.46% [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hostility between nurses at the same level is known as horizontal or lateral violence, which has been defined by some scholars as bullying in this profession. Previous studies have further confirmed the idea that nurses who have experienced horizontal violence can have higher turnover intention (Bashaw, 2019 ; Kabir et al, 2022 ), as explained by Kanter's theory of structural empowerment (Kanter, 2008 ). This theory takes account of three levels of empowerment, that is, the workplace that has the necessary structures to promote empowerment, the psychological belief in one's ability to be empowered, and the acknowledgement of power in the relationships and care that nurses provide (Amor et al, 2021 ; Favaro et al, 2021 ).…”
Section: Introductionmentioning
confidence: 69%
“…Similarly, another study had revealed that horizontal violence could cause HCPs to quit their professions (Bashaw, 2019 ). A survey had also reported higher levels of turnover intention in female nurses who had experienced high levels of horizontal violence (Kabir et al, 2022 ). While there is no exact information on the emigration of Iranian nurses to other countries, a 2021 report published by the Iranian Ministry of Health and Medical Education has acknowledged a sharp increase in the number of such nurses, and the news agencies have made estimates ranging from 1500 to 6000 cases a year, depending on the sources.…”
Section: Discussionmentioning
confidence: 99%
“…The workplace violence scale (WVS) was used to measure the WPV experienced in the last 12 months [ 40 , 41 ]. Several studies used this scale to measure workplace violence among nurses and other health care workers previously [ 42 45 ]. The scale was composed of five types of WPV named physical assault, emotional abuse, threat, verbal and sexual harassment, and sexual assault.…”
Section: Methodsmentioning
confidence: 99%